Production, Characterization, and Activation of Biochars from a Mixture of Waste Insulation Electric Cables (WIEC) and Waste Lignocellulosic Biomass (WLB) - Roberta Mota-Panizio; Ana Assis; Luís Carmo-Calado; Catarina Nobre; Andrei Longo; José Silveira; Maria Margarida Goncalves; Paulo Brito (C, 2023)
Waste insulation electrical cables (WIEC) currently do not have an added value, due to their physical–chemical characteristics. Carbonization is known to enhance feedstock properties, particularly fuel and material properties; as such, this article aimed to study the production and activation of biochars using WIEC and lignocellulosic biomass wastes as feedstock. Biochars were produced in a ceramic kiln with an average capacity of 15 kg at different temperatures, namely 300, 350 and 400 °C. After production, the biochars were further submitted to a washing process with water heated to 95 °C ± 5 °C and to an activation process with 2 N KOH. All biochars (after production, washing and activation) were characterized regarding an elemental analysis, thermogravimetric analysis, heating value, chlorine removal, ash content, apparent density and surface area. The main results showed that the increase in carbonization temperature from 300 to 400 °C caused the produced biochars to present a lower amount of oxygen and volatile matter, increased heating value, greater chlorine removal and increased ash content. Furthermore, the activation process increased the surface area of biochars as the production temperature increased. Overall, the carbonization of WIEC mixed with lignocellulosic wastes showed potential in enhancing these waste physical and chemical properties, with prospects to yield added-value products that activates biochar.